Odpowiedzi

2010-01-08T14:34:08+01:00
B)
(2x²+2x+5x+5)(x-5)-5x+25=0
(2x²+7x+5)(x-5)-5x+25=0
2x³-10x²+7x²-35x+5x-25-5x+25=0
2x³-3x²-35x=0
x(2x²-3x-35)=0
x=0 i 2x²-3x-35=0
Δ=(-3)²-4razy 2razy (-35)
Δ=9+280
Δ=289
pierwiastek z Δ=17

x₁=3-17przez2razy2=-3½
x₂=3+17przez2razy2=5
2010-01-08T14:34:41+01:00
A) 2x³ 3² - 6x +9=0
to dla +
2x³+3²-6x+9=0
2x³+9-6x+9=0
2x³-6x=0 to można rozłożyć na czynniki
2x(x²-3)=0
to dla -
2x³-3²-6x+9=0
2x³+9-6x+9=0
2x³-6x+18=0to też można rozłożyc na czynniki
2(x³-3x+9)=0
b) (2x +5)(x+1)(x-5)-5x+25=0
(2x²+2x+5x+5)(x-5)-5x+25=0
2x³-10x²+2x²-10x+5x²-25x+5x-25-5x+25=0
2x³-3x²-35x=0
x(2x²-3x-35)=0________a=2_b=-3___c=-35
Δ=b²-4ac=(-3)²-4*2*(-35)=9+280=289
x₁=-b-√Δ/2a=3-17/2*2=⁻¹⁴/₄=-3½
x₂=-b+√Δ/2a=3+17/2*2=²⁰/₄=5